Current methods active learning of postgraduate students - Rogachevskiy, O. P.; Popova, L. M.; Rozhkovska, N. M.; Stepanovichus, O. M.; Golubenko, M. Y. (Journal of Education, Health and Sport, 2017)
In the article the experience ofOdessaNationalMedicalUniversityon providing practical training at postgraduate level study. Defined organizational and methodological aspects of the given type of training are implemented complex measures to improve its efficiency. Simulation training technique allows postgraduate students form communicative competence counseling the patient develops the ability to take quick decisions. Accumulation at the Department of Obstetrics and Gynecology №1 experience shows that innovative methods of teaching postgraduate students intensify educational and cognitive activity and expand their creativity, which contributes to effective public policy in health care.